Randomised trial of acid inhibition by vonoprazan 10/20 mg once daily vs rabeprazole 10/20 mg twice daily in healthy Japanese volunteers (SAMURAI pH study). Issue 5 (28th January 2020) - Takeuchi, Toshihisa; Furuta, Takahisa; Fujiwara, Yasuhiro; Sugimoto, Mitsushige; Kasugai, Kunio; Kusano, Motoyasu; Okada, Hiroyuki; Suzuki, Takahiro; Higuchi, Tomohiro; Kagami, Takuma; Uotani, Takahiro; Yamade, Mihoko; et al.
Summary: Background: Vonoprazan (V), a potassium‐competitive acid blocker, has a more durable acid‐inhibitory effect as compared with standard‐dose proton pump inhibitors (PPIs) but has not been compared with 2‐4 times higher daily PPI doses administered in two divided doses. Aims: To evaluate the acid‐inhibitory effect of V 10/20 mg once‐daily (OD; V10/V20) vs rabeprazole (R) 10/20 mg twice‐daily (BID; R20/R40) in healthy Japanese volunteers. Methods: This multicentre, randomised, open‐label, two‐period, crossover study compared V10 or V20 vs R20, or V20 vs R40 using three cohorts of 10 healthy Japanese adults. Within each cohort, subjects were randomised to receive V or R for 7 days and, following a washout period ≥7 days, the other treatment for 7 days. On day 6 of each period, 24‐hours multichannel gastric impedance‐pH monitoring was performed. Percent times pH ≥ 3, ≥4 and ≥5 (pH 3, 4 and 5 holding time ratios [HTRs]) in 24 hours were evaluated as primary pharmacodynamic endpoints. Results: Acid‐inhibitory effect (24‐hours pH 3 HTR) of V20 was greater than those of R20 (91.0% vs 65.3%; P  = .0049) and R40 (98.5% vs 85.9%; P  = .0073). Similar results were obtained for 24‐hours pH 4 and 5 HTRs. V20 also achieved greater nocturnal pH 4 (91.5% vs 73.2%; P  = .0319) and 5 HTRs (78.8% vs 62.2%; P  = .0325) as compared with R40. One subject (20%) developed diarrhoea while receiving R40 which was considered treatment‐related. Conclusions: Compared with 2‐4 times the standard daily dose of R, V20 exerts a more potent and durable acid‐inhibitory effect. Trial identifier: UMIN000022198 (www.umin.ac.jp/ctr/index.htm ).